KOMPENSASI KERJA PADA KARYAWAN CV. JASA SUMBER ASAHAN MEDAN - TASIK UTAMA; RITA WIDIANI; YULIANA .; NGAJUDIN NUGROHO; DEWI ANGGRAINI (LP2MTBM MAKARIOZ, 2019)
Company gives compensation in the form of salary to its employees so that their employees will feel more enthusiastic inworking. This salary will increase employee work performance in a company. The indicators for compensation are consists ofsalary, wages, bonuses, health insurance and pension funds as well as facilities to support one's career development inworking in a company. The formulation of the problem in this study is